Some aspects of daily rainfall distribution over a high range river basin in central Kerala - JAYASREE, V.; KUMAR, K.G. ANIL (MAUSAM, 1997)
ABSTRACT. The daily rainfall distribution of twelve stations in the Chalakudy river basin of central Kerala is studied. Normalised rainfall curve (NRC) is constructed and various parameters of the daily rainfall distribution are derived. The number of rainy days and mean rain intensities at each 10% rain amounts are calculated from the NRC. It has been found that the coefficient of variation (CY) is the most important parameter of the daily rainfall distribution which determines the shape of NRC. Frequency distribution of CY values reveals that the CY is highest in the range of 100-120%. Rainfall contributions by non-rainy days and significant rainfall days are calculated. About half of the seasonal rainfall which contributes 80% of the total rainfall are of low intensity. However, the remaining 20% due to higher intensity rainfall are of considerable significance for floods, erosion, etc.